Comparisons of the Root Mechanical Properties of three Native Mexican Tree Species for Soil Bioengineering Practices - Sánchez Castillo, Laura Margarita; Kubota, Tetsuya; Cantú Silva, Israel; Yáñez Díaz, María Inés; Hasnawir; Pequeño Ledezma, Miguel Angel (Sociedad Botánica de México, 2017)
Abstract Background: Urbanized slope areas in Sierra Madre Oriental are prone to sediment related disasters mainly caused by heavy rainfall episodes during hurricane season, knowledge on the factors on soil-roots dynamics are required to mitigate or lessen those disasters. Questions and hypothesis: The mechanical properties of roots of native species vary according species. The mechanical properties of the roots are influenced by the morphology of root: diameter. Species studied: Quercus rysophylla, Pinus pseudostrobus and Acacia berlandieri. Study site and dates: Sierra Madre Oriental, Chipinque Ecological Park in Monterrey, Nuevo Leon. From middle of December 2014. Methods: Selection of species was made base on widespread distribution and predominance in degraded areas. Samples were taken at field and tensile tests to calculate maximum force to root breakage were conducted using a laboratory dispositive, calculations of tensile strength and modulus of elasticity were calculated using formulas. The corresponding relations between root diameter and mechanical properties were established. Results: Results confirmed that bigger diameters require bigger forces to break. In other hand, results confirmed the negative relationship between diameter and tensile strength and diameter and modulus of elasticity. Pointing out that roots of bigger diameter have less tensile strength and elasticity. The order of importance of the species studied according its mechanical properties was found like: Acacia berlandieri > Quercus rysophylla > Pinus pseudostrobus. Conclusions: The results of this study begin the data contribution of the mechanical properties of native species of Sierra Madre Oriental in order to use it in the application of soil bioengineering practices on urbanized slopes prone to disasters. Keywords: Root mechanical properties, native forest species, soil bioengineering, landslides, Sierra Madre Oriental